University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.3 - Differentiation Rules - Exercises - Page 135: 7


$w'= -6z^{-3} +z^{-2}$ $w'= 18z^{-4} -2z^{-3}$

Work Step by Step

$w= 3z^{-2} - \frac{1}{z}$ $w'= -6z^{-3} +z^{-2}$ $w'= 18z^{-4} -2z^{-3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.